고온고습환경이 Sn계 무연솔더의 부식 및 기계적 특성에 미치는 영향 - 김정아(Jeonga Kim); 박유진(Yujin Park); 오철민(Chul Min Oh); 홍원식(Won Sik Hong); 고용호(Yong-Ho Ko); 안성도(Sungdo Ahn); 강남현(Namhyun Kang) (Journal of welding and joining, 2017)
The effect of high temperature-moisture on corrosion and mechanical properties for Sn-0.7Cu, Sn-3.0Ag-0.5Cu (SAC305) solders on flexible substrate was studied using Highly Accelerated Temperature/Humidity Stress Test (HAST) followed by three-point bending test. Both Sn-0.7Cu and SAC305 solders produced the internal $SnO_2$ oxides. Corrosion occurred between the solder and water film near flexible circuit board/copper component. For the SAC305 solder with Ag content, furthermore, octahedral corrosion products were formed near Ag3Sn. For the SAC305 and Sn-0.7Cu solders, the amount of internal oxide increased with the HAST time and the amount of internal oxides was mostly constant regardless of Ag content. The size of the internal oxide was larger for the Sn-0.7Cu solder. Despite of different size of the internal oxide, the fracture time during three-point bending test was not significantly changed. It was because the bending crack was always initiated from the three-point corner of the chip. However, the crack propagation depended on the oxides between the flexible circuit board and the Cu chip. The fracture time of the three-point bending test was dependent more on the crack initiation than on the crack propagation.